Construction and Evaluation of Aminophylline Ion-Selective Electrode in its Pharmaceutical Preparations and Biological Fluids - SHALABY, ABDALLA; I. ABDULRAHEEM, ABDULKAREEM; EL-MAAMLY, MAGDA; EL-TOHAMY, MAHA (Asian Journal of Chemistry, 2010)
A PVC membrane electrode of aminophylline and tungstophosphoric acid association complex was constructed. The basic electrode's performance characteristics were evaluated. The prepared electrode exhibits a Nernstain response (19.6 ± 0.2 mV/decade) over the concentration range of aminophylline 1 × 10-2–5 × 10-6 M of solutions of pH 4-7. Common organic and inorganic cations showed negligible interference. Direct potentiometric determination of 1 × 10-2–5 × 10-6 M aqueous aminophylline using this membrane electrode system showed an average recovery of 99.80 with mean standard deviation ± 0.919. The electrode gave a good stability reproducibility and fast response. These characteristics of the electrode enable it to be used successfully for the determination of aminophylline in pure form, pharmaceutical preparations and in biological fluids.